The Post Conflict Fund : Addressing Challenges of Globalization - An Independent Evaluation of the World Bank’s Approach to Global Programs - Bahnson, Caroline; Cutura, Jozefina (World Bank, Washington, DC, 2016)
The Operations Evaluation Department (OED) is an independent unit within the World Bank. The goals of evaluation are to learn from experience, to provide an objective basis for assessing the results of the Bank’s work, and to provide accountability in the achievement of its objectives. This report on the Post-Conflict Fund (PCF) is one of twenty six case studies that have been prepared as source material for the second phase of OED’s independent evaluation of the Bank’s involvement in global programs. The program objective is to position the Bank through constructive engagement in conflict-affected countries where normal instruments and budget provisions cannot apply. The key findings are as follows : (i) a flexible instrument such as the PCF serves the needs that the Bank’s numerous instruments do not fulfill in conflict-affected countries; (ii) yet if the policy guidelines under which it operates are too flexible, and the DGF criteria are ambiguous and insufficiently enforced, the instrument can be less than fully effective; (iii)Programs can continue over several years without a results-based framework and strong monitoring and evaluation; (iv) as currently designed, the country-by-country approach of the program does not sufficiently generate broader cross-country lessons and does not exploit the program’s full potential to serve the Bank and its partners strategically; and (v) a global partnership program on conflict-affected countries with partners at the governance level might help the Bank, United Nations (UN) agencies, and other stakeholders to better respond to the transition from relief, to rehabilitation and reconstruction and development. Finally, this being an OED evaluation, it focuses primarily on the Bank’s strategic role and performance in playing up to its comparative advantage relative to other partners in each program.